Socio-economic transformations in the Baltic countries - Natalia V. Govorova (Научно-аналитический вестник Института Европы РАН)
Anti-Russian sanctions have turned into a serious challenge for the economy and social model of the countries of the Baltic-Scandinavian macroregion, which includes the Baltic states. Higher prices for food and basic services, electricity bills, increased mortgage rates and rents have reduced the standard of living and quality of life of a significant part of the population of the Baltic states. Rising cost of living, poverty and social exclusion have become the most significant problems for the population in recent years. A sharp jump in inflation at the turn of the 2020s has led to a deeper cost of living crisis than the European Union average. This is evidenced by the statistical data reviewed by the author, studies by domestic and Western economists, and public opinion polls. The analysis of the dynamics of socio-economic development of the Baltic States, conducted in order to assess the prospects for the further course of the relevant processes in the region, has shown that socio-economic transformations in Estonia, Latvia and Lithuania were regressive, uneven not only in the country context, but also differed significantly depending on the characteristics of households within the countries. The difference in the level of cost-of-living inflation for the poorest and richest households has increased in recent years. The economic and political spaces of the Baltic states, against the background of high inflation and close to stagnation GDP growth rates, nevertheless demonstrated different results in terms of certain socio-economic parameters, which is largely due to the difference in the provision of their own energy resources and measures taken at the national level to mitigate the crisis phenomena.